Online Buying Behaviour among Youth: A Multigroup Analysis Based on Gender - Umi Julaihah (Jurnal Economia, 2026)
This study intended to explore the effect of financial literacy, social media use, and pay-later promotion on online impulsive and compulsive buying among youth. 366 valid responses were analysed with partial least squares structural equation modelling (PLS-SEM). Further, moderation using multigroup analysis (MGA) was conducted to gain a deeper understanding of whether gender differences are present in the model proposed. The finding revealed that only the use of social media had a positive and significant effect on impulsive online buying, and impulsive buying became crucial determinants for compulsive buying. Further, this study also confirmed that buying behavior between males dan females had no significant difference. This study showed no significant effect of financial literacy on buying behaviour among youth, which could be due to the respondents' low level of financial knowledge of respondents.